Mudanças percebidas na relações familiares e de amizade por mulheres de meia-idade cursando a universidade - Leonel, Sandra Bomfim (2013)
Given the number of women aged over 40 years, corresponding to 35% of the total Brazilian female population, there is a growing interest of women in this age group to join a university searching for new opportunities and knowledge. Thus, based on the work of Hinde about interpersonal relationships, this work aimed to investigate perceived changes in the family relationships and friendships of middle-aged women, married with children, after their insertion in a undergraduate course at the Federal University of Espírito Santo. The perceived changes in relationships with family members (spouse and children), in relationships with old friends and establishing new friendships after their university entrance have been investigated. Eight women aged between 40 and 60 years, regular undergraduate students at UFES have been interviewed. Data were collected through semi-structured interviews and analyzed qualitatively. The results were divided into topics emphasizing the expectations and challenges in returning to studies, the influence of academic life in everyday practice, in family relations and in friendships, the future plans of the mother / wife in the eyes of family members, the meaning of academic life for the middleaged woman. It was found that the university entrance was permeated by conflicts, prejudices, and accumulation of functions and stress besides personal achievement, intellectual growth, the development of new friendships and reframing of life.